Assessment of Kali River Water Pollution -A Quantitative Approach - Ram, Ramakant; Sinha, DK; Kumar, Navneet (Asian Journal of Biological and Life Sciences, 2012)
A quantitative approach for the assessment of Kali river water pollution has been carried out on the basis of calculated values of water quality indices(W.Q.I.). Water quality index for nine sites has been calculated with the help of estimated values of ten different water quality parameters and drinking water standards prescribed by World Health Organization(W.H.O.). River water was found to be severely polluted at all the sites of study with W.Q.I. values more than 100. People exposed to water of source of study are prone to health hazards of polluted water. Calculated higher values and estimated values of different parameters both verify the extent of water pollution. Hence, assessment of water quality on the basis of calculated values of W.Q.I. is proved to be an effective tool.